War, Military Service, and Union Formation in Northern Vietnam - TEERAWICHITCHAINAN, Bussarawan (Institutional Knowledge at Singapore Management University, 2012)
As wars exert increasing force on global affairs, there is greater demand for understanding the international diversity of family experiences with conflicts. This study examines the relationship between military participation during the Vietnam War (1965-1975) and first-marriage timing among northern Vietnamese men and women. Based on the Vietnam Longitudinal Survey and its recent followup, this paper describes cohort variations in the likelihood and timing of first marriage during pre-war, wartime, and post-war years and addresses the effects of veteran status, combat exposure, duration and timing of service. We find war did not decrease marriage likelihood among men but caused significant delays in first-marriage among veterans. Except for urban women, female first-marriage timing was largely immune from war impacts. Parental role in mate selection, residential propinquity, and postnuptial living arrangement helped facilitating wartime union formation. We extend the present discussion of marriage resilience to shed light on Vietnam’s current marriage trends and the “flight from marriage” patterns in Pacific Asia.